2021
DOI: 10.1101/2021.07.19.21260635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public opinion on sharing data from UK health services for clinical and research purposes without explicit consent

Abstract: BACKGROUND. In the UK, National Health Service (NHS/HSC) data is variably shared between healthcare organizations for direct care, and increasingly used in de-identified forms for research. Few large-scale studies have examined public opinion on sharing, including the treatment of mental health (MH) versus physical health (PH) data. METHODS. Pre-registered anonymous online survey open to all UK residents, recruiting Feb-Sep 2020. Participants were randomized to one of three framing statements regarding MH vers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…People in our study were motivated to share their information if their security number and telephone number were not gathered (75.2%), which gives them a sense of security and privacy. The use of de-identified data for research purposes was a strong motive for participants in the United Kingdom health service [ 29 ]. Weitzman et al revealed that 90% of people enrolled in their study were willing to share their data for research if rigorous confidentiality measures were implemented [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…People in our study were motivated to share their information if their security number and telephone number were not gathered (75.2%), which gives them a sense of security and privacy. The use of de-identified data for research purposes was a strong motive for participants in the United Kingdom health service [ 29 ]. Weitzman et al revealed that 90% of people enrolled in their study were willing to share their data for research if rigorous confidentiality measures were implemented [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These have identified that there is typically a low understanding of research methods and the value linked records can bring; but, once individuals understood the purpose and potential benefits of using data in research, then this is typically supported on the condition that the research is intended to benefit the public good and that sufficient safeguards are in place [9][10][11][12]. However, there is a varying degree of trust placed in different organisations for the use of data in this way, and the type of organisation deemed most trustworthy is context specific [13,14]. Within longitudinal studies, Stockdale and colleagues' [15] systematic review on public attitudes towards the use of patient data identified a complexity of views and a low level of awareness regarding the secondary use of health and other records in research.…”
Section: Introductionmentioning
confidence: 99%